Tempo Livre e Lazer na África sob Domínio Colonial Alemão - Sílvio Marcus de Souza Correa (Cadernos de Estudos Africanos)
Leisure in Africa under German colonial rule has a short history of three decades. The leisure was almost a privilege of whites during the colonial era. But some Africans were supporting the sports practices or leisure of white. Without the assistance of “natives” would not be possible to practice some sports or forms of recreation in the colonial context. Leisure also fostered aspirations among Africans and varied by region, ethnic, social or religious group, as well as the age or gender of individuals. The practice of sporting or leisure activities had an aggregate effect on the subaltern groups.